PENGARUH RETURN ON ASSETS, LEVERAGE, UKURAN PERUSAHAAN, INTENSITAS ASET TETAP DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK - Espi Noviyani; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
This study aims to examine the factors that affect the company’s tax avoidance using effective tax avoidance as an indicator. There are several factors used in this research consisted of return on assets, leverage, size, capital intensity and institutional ownership. The purpose of this study is to empirically examine whether the return on assets, leverage, size, capital intensity and institutional ownership affect the tax avoidance in manufacturing companies listed in Indonesia Stock Exchange. The result showed that return on assets, leverage, capital intensity and institutional ownership significantly affect tax avoidance. Meanwhile size does not significantly influence tax avoidance. In this study there are still many limitation and shortcomings namely the effect of independent variables on the dependent variables can only explain by 12.7%. Hence, more independent variables are needed.